2010
DOI: 10.1002/jor.21108
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between intact and antibiotic‐inactivated bacteria by real‐time PCR after treatment with propidium monoazide

Abstract: One limitation to the use of the polymerase chain reaction (PCR) to identify orthopedic infections has been apparent falsepositive results, possibly due to the detection of dead bacteria. We recently showed that the use of DNA-binding agent propidium monoazide (PMA) could distinguish viable from heat-inactivated bacteria, and, in this study, we investigated whether the same technique can be applied to bacteria killed by two antibiotics with distinctly different mechanisms of action, a test of greater clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Recently, PMA‐qPCR was used to identify intact cells from antibiotic‐inactivated Staphylococcus aureus and S. epidermidis with vancomycin and gentamicin (Kobayashi et al ., 2010). This study reported that the C t difference ( Ct with PMA – Ct without PMA ) under gentamicin treatments increased gradually, but decreased after a 24 h of incubation, indicating that the number of viable bacteria had increased and was still present after a 24 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PMA‐qPCR was used to identify intact cells from antibiotic‐inactivated Staphylococcus aureus and S. epidermidis with vancomycin and gentamicin (Kobayashi et al ., 2010). This study reported that the C t difference ( Ct with PMA – Ct without PMA ) under gentamicin treatments increased gradually, but decreased after a 24 h of incubation, indicating that the number of viable bacteria had increased and was still present after a 24 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…The interference of antibiotics with the cell wall and periplasm membrane synthesis might affect the PMA treatment because the DNA‐binding chemical is a membrane‐impermeant dye that selectively penetrates cells with compromised membranes, which can be considered dead cells (Nocker et al ., 2006). A previous study also showed that vancomycin (inhibition of cell wall synthesis) was more efficient at inhibiting PCR amplification on PMA treatment than gentamicin (Kobayashi et al ., 2010). Thus, PMA‐qPCR could be used to discriminate VBNC from antibiotics‐inactivated bacteria cells when antibiotic pressure induces the VBNC state in P. aeruginosa PAO1, which is known to be an opportunistic pathogen‐ and antibiotic‐resistant bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…PMA purchased from Biotium Inc. (Biotium, Hayward, CA, USA) was added at a final concentration of 50, 25, 10, or 2.5 mg/ml to sample tubes containing 300 ml of either viable (100% controlled viable sample) or heat-killed (0% controlled viable sample) cells (10 5 CFU/ml), as described in previous studies (Kobayashi et al 2009b(Kobayashi et al , 2010. For PMA staining, the tubes were placed in the dark for 5 min and then transferred to ice and exposed to a 500 W halogen light at a distance of 20 cm.…”
Section: Optimization Of the Pma Treatmentmentioning
confidence: 99%
“…In contrast, PMA can only penetrate dead cells and has therefore been recommended as a highly selective dye to distinguish S. aureus that have been inactivated by heat or antibiotics from living bacteria (Kobayashi et al 2009b(Kobayashi et al , 2010. These results indicate that while EMA and PMA present similar mechanisms for discriminating between viable and dead bacteria, the penetration of these two dyes into bacteria could be species-dependent.…”
Section: Introductionmentioning
confidence: 96%
“…Inactivation under conditions such as scenarios 3 and 4 in Table 1 can lead to an overestimation of the viable cell population. Reported examples include photoinactivation of Enterococcus faecalis (53), UV inactivation of E. coli O157: H7, Salmonella, and Campylobacter (34, 38), low-temperature pasteurization of Listeria innocua (54), and aminoglycoside treatment of Staphylococcus species (55). There can be challenges even under scenario 2 (Table 1).…”
mentioning
confidence: 99%